2015
DOI: 10.1159/000430917
|View full text |Cite
|
Sign up to set email alerts
|

A 15-Year Nationwide Epidemiological Analysis of Guillain-Barré Syndrome in Taiwan

Abstract: Background: Guillain-Barré syndrome (GBS) is a potentially life-threatening disease that typically occurs after a preceding infectious disease. An accurate estimation of GBS incidence would be useful for investigating the potential causal relationships between risk factors and GBS. Here we described the nationwide incidence of GBS in Taiwan. Methods: The cases of GBS were obtained from all admission records of the National Health Insurance Research Database. We identified all of the first-admitted GBS patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 27 publications
11
22
0
1
Order By: Relevance
“…This study discovered a gradual increase in GBS incidence over the assessed 12‐year period, which went from 1.61 to 2.35/100,000. These results were consistent with previous studies that calculated an increasing trend for GBS over the past several years (Shui et al, ; Huang et al, ) . The lowest incidence was in 2001 (1.61/100,000); however, the loss of data might be possible because the system of registry of DEIS started this year.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This study discovered a gradual increase in GBS incidence over the assessed 12‐year period, which went from 1.61 to 2.35/100,000. These results were consistent with previous studies that calculated an increasing trend for GBS over the past several years (Shui et al, ; Huang et al, ) . The lowest incidence was in 2001 (1.61/100,000); however, the loss of data might be possible because the system of registry of DEIS started this year.…”
Section: Discussionsupporting
confidence: 94%
“…Concerning gender distribution, GBS presented a higher IR in men than women, with a male to female ratio of 1.47 : 1. This ratio is consistent with other national database studies, such as those by Huang and coworkers (Huang et al, 2015) in Taiwan (1.54 : 1) and Shui and coworkers ( 2012) (Shui et al, 2012) in the United States (1.41 : 1).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Patterns of IR with respect to age and sex distributions in adults were similar to those observed in other populations (Sejvar et al , ; Shui et al , ; Hense et al , ; Benedetti et al , ; Huang et al , ) . In particular, in a German study based on 889 GBS cases, a more marked increase in the incidence of GBS was observed after the age of 50 which reached a peak between the ages of 70 and 79 (Hense et al , ) .…”
Section: Discussionsupporting
confidence: 85%
“…Although the pathogenesis of GBS remains somewhat unknown, there is increasing indication that it is an autoimmune disease, evoked by an antecedent infection cross-reaction with peripheral nerve components because of molecular mimicry [3,4]. …”
Section: Introductionmentioning
confidence: 99%